(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
A heat and moisture transfer model for the clothed human body is developed based on the 3-D scanning data of the human body. The whole passive clothed human body system is subdivided into four sub- systems which are the tissue system, the circulatory system, the respiratory system and the clothing system. The physical process of the heat and moisture transfer in the each sub-system is described by energy and mass balance equations. The Finite Element Method (FEM) is used to solve the governing equations for each sub-system. For a multi-layer clothing sub-system, a simple solution scheme is given by defining the air element. Also, the model is validated by comparing the simulation with experimental results from the literature. Finally, the 3-D simulation results are shown. The conclusion shows that the model has good prediction ability and it can be applied in the clothing design.